2017
DOI: 10.1111/aji.12728
|View full text |Cite
|
Sign up to set email alerts
|

Placental pericytes and cytomegalovirus infectivity: Implications for HCMV placental pathology and congenital disease

Abstract: Problem Placental pericytes are essential for placental microvascular function, stability, and integrity. Mechanisms of HCMV pathogenesis incorporating placental pericytes are unknown. Method of Study HCMV infected placental tissue was stained by dual-labeled immunohistochemistry. Primary placental pericytes, cytotrophoblasts, and villous fibroblasts were exposed to HCMV; infectivity was analyzed by microscopy and immunofluorescence. Cytokine expression was examined by Luminex assay. A HCMV-GFP recombinant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
(53 reference statements)
1
26
0
Order By: Relevance
“…Given that the main mediators for cell entry of SARS-CoV-2 were minimally expressed by the human placenta, we also investigated whether the receptors for congenital viruses such as CMV ( Stegmann and Carey, 2002 ; Arechavaleta-Velasco et al, 2002 ; Aronoff et al, 2017 ; Pereira et al, 2017 ; Al-Haddad et al, 2019 ; Faure Bardon et al, 2020 ) and ZIKV ( Coyne and Lazear, 2016 ; Adams Waldorf et al, 2016 ; Aldo et al, 2016 ; Cao et al, 2017 ; Aagaard et al, 2017 ; Mysorekar, 2017 ; Valentine et al, 2018 ; Adams Waldorf et al, 2018 ; Dudley et al, 2018 ; Walker et al, 2019 ; Nelson et al, 2020 ), which are known to infect and cross the placenta, were detectable using our pipeline. Known receptors for CMV include NRP2 ( Martinez-Martin et al, 2018 ), PDFGRA ( Martinez-Martin et al, 2018 ), and CD46 ( Stein et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that the main mediators for cell entry of SARS-CoV-2 were minimally expressed by the human placenta, we also investigated whether the receptors for congenital viruses such as CMV ( Stegmann and Carey, 2002 ; Arechavaleta-Velasco et al, 2002 ; Aronoff et al, 2017 ; Pereira et al, 2017 ; Al-Haddad et al, 2019 ; Faure Bardon et al, 2020 ) and ZIKV ( Coyne and Lazear, 2016 ; Adams Waldorf et al, 2016 ; Aldo et al, 2016 ; Cao et al, 2017 ; Aagaard et al, 2017 ; Mysorekar, 2017 ; Valentine et al, 2018 ; Adams Waldorf et al, 2018 ; Dudley et al, 2018 ; Walker et al, 2019 ; Nelson et al, 2020 ), which are known to infect and cross the placenta, were detectable using our pipeline. Known receptors for CMV include NRP2 ( Martinez-Martin et al, 2018 ), PDFGRA ( Martinez-Martin et al, 2018 ), and CD46 ( Stein et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, cytomegalovirus (CMV) infection results in a disturbance of placental angiogenesis (21), which was related to infection of placental pericytes (22). Furthermore, endothelial cells infected with CMV displayed an aberrant vascular morphology (23) and exhibited elevated levels of leukotriene B4 and 5-lipoxygenase (24).…”
Section: Discussionmentioning
confidence: 99%
“…This may affect retinal neurovascular permeability as well as an increase in retinal inflammation and angiogenesis [12]. Previous studies by Alcendor et al and Wilkerson et al showed vascular pericytes to be the most permissive cell type to HCMV infection within the BBB and the IBRB [11,16]. These findings suggest that vascular pericytes may serve as amplification reservoir for HCMV dissemination within these vascular beds.…”
Section: Cytomegalovirus and Retinal Pericytes: Implications In Ocmentioning
confidence: 99%
“…Placental pericytes are essential for endothelial cell proliferation as well as for placental microvasculature stability and integrity but have largely been ignored in placenta biology. Pericytes are also critical for placental vascular development and angiogenesis [15,16,17,18,19]. Mesangial cells are considered specialized pericytes of the renal glomerulus [20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%